Promotion of Tourism in Uttaranchal - Kumar Sharma, Dr. Jugendra (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
This paper focuses on the sustainable promotion of Tourism in Uttaranchal. Uttaranchal is a state in the Northern Himalayan Region in India and it has been a hot spot of tourism due to its magnificently diverse landscapes, high biodiversity, enough religious tourist potential and rich cultural heritage, which has also generated a good source of income and employment to youths and rural masses.Uttaranchal state is famous for its natural beauty and pilgrims have been attracted to the region for many centuries. There are situated four dhams which create attraction for domestic, as well as international tourists. Tourism is one of the biggest attractive and fastest growing economic sectors in the global economy and has significant environmental, cultural, social and economic effects, both positive and negative. The Garhwal Mandal Vikas Nigam (GMVN) and the Kumaon Mandal Vikas Nigam (KMVN) Both Nigam are set up for promoting tourism and earning substantial revenue for sustainable development of Uttaranchal economy. Promotion of Tourism can be taken in four different interpretations that include economic promotion of tourism, the ecologically sustainable tourism, sustainable tourism development and market and publicity. Therefore, the purpose of this research is to adopt integrated approach and establishment of new plans for the sustainable development of tourism in Uttaranchal and finally to synthesis all the findings and give feasible suggestions and recommendations for further development of tourism in this region. Keywords:- Promotion of tourism, sustainable development, cultural, environmental, integrated approach